Standardization of Alternative Methods for Nanogenotoxicity Testing in Drosophila melanogaster Using Iron Nanoparticles: A Promising Link to Nanodosimetry - Venkatachalam Deepa Parvathi; Kalyanaraman Rajagopal; Ravindran Sumitha (Journal of Nanotechnology)
The remarkable advancement of nanotechnology has triggered enormous production of metal nanoparticles and nanomaterials for diverse applications in clinical diagnostics and biomedical research. Nanotechnology has facilitated understanding and analysing nanotoxicology in a holistic approach. Iron nanoparticles have been of special interest in recent research owing to their dynamic, paramagnetic, and catalytic properties. Research studies (in vitro model) have demonstrated the lack of toxicity in nanoiron. The present study design involves in vivo toxicity assessment of nanoiron at specific concentrations of 0.1 mM, 1 mM, 5 mM, and 10 mM in Drosophila. DNA fragmentation assay in exposed and F1 population showed first-line toxicity to flies. Viability and reproductive ability were assessed at 24-hour and 48-hour intervals and thus indicated no statistical significance between the exposed and control groups. The wing spot assay has expressed transparent lack of toxicity in the studied concentrations of nanoiron. Protein profiling has demonstrated that the protein profiles have been intact in the larvae which confirm lack of toxicity of nanoiron. This leads to concluding that nanoiron at the defined concentrations is neither genotoxic nor mutagenic.